Effect of Pin Diameters on the Wear Characteristics of Friction Pairs - Wei, Y.H.; Wang, X.L.; Liu, Y.P.; Chen, L.J. (Проблемы прочности, 2019)
The tribological tests are carried out to assess the effect of pin diameters on wear characteristics via changing contact stresses and sliding speeds to provide support for choosing friction pair sizes. The friction couple is set as CuZn pins for medium carbon steel (No. 1045 steel) rings. The differential wear rate and its calculation formula are defined to express the line wear rate or the wear resistance of unit cross-section area. The effect of the pin end surface diameter on differential wear rate and its scale/increased multiplier are investigated. When the product (P×V=0.095) is kept constant, the abrasion loss for the specimens of a small diameter (d1=0.6 mm) is lesser than that of the specimens of a large diameter (d2=4.0 mm). As compared to the sliding speed, the change in contact stresses exerts a greater influence on the wear behavior, especially for small-diameter specimens. The differential wear rate of small-diameter specimens is always higher than that of the specimens of a large diameter. The scale multiplier of the differential wear rate is always larger than that of the contact pressure stress, especially for small-diameter specimens.